Effect of fatigue on lower extremity symmetry in recreational runners - Hanyu, Pan (2024)
Running is one of the most popular physical activities in the world. However, running is an impact activity that can lead to overuse injuries such as tibia stress fractures and patellofemoral pain syndrome. It is reported that both inter-limb asymmetries and fatigue are risk factors for non-contact injuries (Heil et al., 2020). Thus, this thesis aimed to examine the impact of running-induced fatigue on lower extremity symmetry in recreational runners. Twenty recreational runners were recruited in this study. Participants performed a fatigue protocol on a motorized treadmill, marker trajectories were collected before and after the fatigue protocol using a Vicon eight-camera motion capture system. OpenSim (Delp et al., 2007) was used for calculating hip, knee, and ankle joint kinematics. Inter-limb asymmetries can be analyzed using discrete and continuous methods. Symmetry angle (SA) is the measurement to quantify the differences between the lower extremities. SA serves as a robust tool since it is a dimensionless metric without the reference number. A Wilcoxon signed-rank test was used to compare the SA for joint angles before and after fatigue protocol. In comparison, Statistical parametric mapping (SPM) as a continuous analysis was applied to the pre- and post-fatigue measurement to analyze the time series data. After fatigue, the SA of the hip peak abduction angle significantly decreased by 7.9% after the running-induced fatigue protocol (p=0.021). Meanwhile, the SA of peak internal rotation after fatigue was significantly higher (9.8%) than that before fatigue (p=0.023). However, SPM results failed to show any difference in the pre- and post-fatigue measurements between the limbs. Although SA has been successfully proved as a reliable indicator to quantify symmetry, future studies should consider continuity by using time-series symmetry indices.